Wages and Higher Education Participation - ELEFTHERIOU, Konstantinos; ATHANASIOU, George; PETRAKIS, Panagiotis (Journal of Research in Educational Sciences; Vol 1 No 1 (2010): JRES Volume I Issue 1(1) Summer 2010, 2010)
The paper develops a model for the screening mechanism for higher education, within an adverse selection framework. Specifically it examines the effect of wage earned by high school graduates on higher education participation. The model pinpoints a positive relation between the “high school” wage and the number of candidates entered in higher education with positive influences on the quality of selection mechanism. An empirical examination is conducted, using U.S. data, in order to investigate the validity of our analytical results.